Extended phenotype in action. Two possible roles for silica needles in plants: not just injuring herbivores but also inserting pathogens into their tissues. (3rd July 2019) - Lev-Yadun, Simcha; Halpern, Malka
ABSTRACT: Phytoliths are silica bodies of various shapes including in the shape of sharp needles formed by many land plants. Defense from herbivory is one of the several known functions of phytoliths, especially the mechanical defense by abrasion of the mouthparts of arthropods and the teeth of mammalian herbivores. Another, although somewhat lesser-known, anti-herbivory defensive mechanism of phytoliths is wounding by sharp silica needles. We discuss and illuminate an even much less known defensive mechanism by phytoliths, i.e., the ability of needle-like phytoliths to insert microscopic pathogens (bacteria, fungi, viruses) into herbivores' tissues. We do it by comparison and by showing analogy with the better-known insertion of microbial pathogens into the body of herbivores by thorns, spines, and prickles. This largely overlooked and understudied defensive mechanism is a special case of a double extended phenotype; plants' defense, and the multiplication and dispersal of microorganisms, and is thus a case of mutualism.